Mitigation of Voltage Sag for Different Types of Fault by Using Dynamic Voltage Restorer (DVR) - Mohd Ghazali, Muhamad Amir Ridhuan; Soomro, Dur Muhammad (Evolution in Electrical and Electronic Engineering, 2023)
The power Quality (PQ) problem is a crucial study in electrical power, and it can be defined as changes in amplitude, frequency, and waveform in a voltage and current. Voltage sag is one of the PQ problems that commonly occurs in power systems, and it is usually caused by Three Phase Fault (TPF) and switching on heavy loads. The aim of this project is to modify the IEEE 5 busbar network system and simulate it in MATLAB Simulink, to create the voltage sag in the modified system, and to mitigate the voltage sag created by using a Discrete Fourier Transform (DFT) controlled Dynamic Voltage Restorer (DVR). The voltage sag was created by applying TPF using the Three Phase Fault block in Simulink and switching on heavy load was created by connecting the heavy load to the modified system using the Three Phase Breaker block in Simulink. The result shows that the voltage sag created by using TPF was 50.1%, and 20.5% for switching on heavy load in the modified system and it was successfully mitigated by using the DFT-controlled DVR.